2011
DOI: 10.5588/ijtld.10.0539
|View full text |Cite
|
Sign up to set email alerts
|

Predicting mortality in hospitalized patients with 2009 H1N1 influenza pneumonia

Abstract: The decision to hospitalize a patient with CAP due to 2009 H1N1 influenza should not be based on current CAP severity scores, as they underestimate mortality rates in a significant number of patients. Patients with obesity or wheezing should be considered at an increased risk for mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 9 publications
3
35
1
Order By: Relevance
“…Wheezing is one of the manifestations of asthma and a previous report indicated that wheezing is associated with influenza mortality [16]. In the present study, total 43.8% of subjects presented wheezing and 33.7% presented both pneumonia and wheezing.…”
Section: Discussionsupporting
confidence: 59%
“…Wheezing is one of the manifestations of asthma and a previous report indicated that wheezing is associated with influenza mortality [16]. In the present study, total 43.8% of subjects presented wheezing and 33.7% presented both pneumonia and wheezing.…”
Section: Discussionsupporting
confidence: 59%
“…Three of the most common clinical scores-CURB-65, APACHE II, and SOFA-were evaluated, all of which have been used to evaluate the severity of viral and bacterial CAP (15,19,31). Recently, studies demonstrated that CURB-65 is not a good predictor of the severity of pneumonia caused by influenza A (H1N1)pdm09 (29,36). In a previous study, the authors demonstrated that the SOFA score was the best severity predictor in CAP cases, including those patients infected with influenza A (H1N1)pdm09 (32), similar to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in the most recent H1N1 epidemic, cigarette smoking increased the risk for hospitalization in the context of this illness (65), further adding to the clinical relevance of this association. Chronic exposure to alcohol in animal models enhances the severity of influenza infection (35) and has also been associated with the development of seasonal influenza, but not specifically H1N1 (47). Improved understanding of the relationship between smoking, AUDs, and influenza could be important given pneumonia that commonly occurs after primary influenza infections.…”
Section: Discussionmentioning
confidence: 99%